Transferring ELT Knowledge to the Classroom – Results of a Study - Koblowska, Magdalena (Glottodidactica, 2006)
The author has been struggling with problems, the most worrying of which ahs always been the students’ inability to transfer the knowledge and skills they should have acqui ed during the course to the English language classroom. In an attempt to find out the possible reasons for such a situation the author made a small-scale survey, the results of which are presented below.